2015
DOI: 10.1016/j.buildenv.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

A new method to assess spatial variations of outdoor thermal comfort: Onsite monitoring results and implications for precinct planning

Abstract: a b s t r a c tResidents wish to have outdoor spaces to enjoy walking, cycling, and other recreational activities, which are often hindered by the unfavorable thermal comfort conditions, especially in the summer. High building densities lower the average wind speed and this intensifies the urban heat island effects at city scale. The conscientious use of building morphology to create local thermal comfort zone at selected spots in a large precinct is becoming a pressing issue for sustainable urbanization. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(55 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…Step 2: based on the obtained basic information, the wind environment at pedestrian level can be obtained by field measurements (Jones et al, 2000;Niu et al, 2015), wind tunnel tests (Du, Mak, Huang et al, 2017;Kubota et al, 2008;Tsang et al, 2012) or computational fluid dynamics (CFD) simulations (Blocken, Janssen, & van Hooff, 2012Du, Mak, Liu et al, 2017;Du, Mak, & Ai, 2018;Tominaga, Mochida, Murakami, & Sawaki, 2008). The field measurements should be conducted for a long time due to the uncertainty and unsteadiness of meteorological conditions (Schatzmann & Leitl, 2011;Schatzmann, Rafailidis, & Pavageau, 1997).…”
Section: Design Framework and Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Step 2: based on the obtained basic information, the wind environment at pedestrian level can be obtained by field measurements (Jones et al, 2000;Niu et al, 2015), wind tunnel tests (Du, Mak, Huang et al, 2017;Kubota et al, 2008;Tsang et al, 2012) or computational fluid dynamics (CFD) simulations (Blocken, Janssen, & van Hooff, 2012Du, Mak, Liu et al, 2017;Du, Mak, & Ai, 2018;Tominaga, Mochida, Murakami, & Sawaki, 2008). The field measurements should be conducted for a long time due to the uncertainty and unsteadiness of meteorological conditions (Schatzmann & Leitl, 2011;Schatzmann, Rafailidis, & Pavageau, 1997).…”
Section: Design Framework and Guidelinesmentioning
confidence: 99%
“…The results showed that a small gross coverage ratio should be adopted in city planning because a high gross coverage ratio results in low wind velocity at pedestrian level, especially for the detached houses. Niu et al (2015) conducted field measurements in a university campus in Hong Kong, and their findings indicated that local wind amplification could be achieved by utilising an innovative building design (lift-up design). numerically studied the wind environment in idealized high-rise urban areas, and reported that building height variation could improve pedestrian level wind environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research was conducted on parks and streets to identify the current problems, and improvement plans using green space planning approaches were explored. Changes in the thermal environment were examined by applying various design factors [13][14][15][16][17][18]. Field studies and experiments, surveys of pedestrians, and programs to evaluate the improvement in thermal comfort have been conducted [19][20][21][22][23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ashie and Kono [19] and Tominaga et al [20] utilized k-ε models to investigate the urban outdoor thermal environment for mitigating the microclimate. Liu and Niu et al [21,22] analyzed the thermal comfort condition underneath an elevated building by using the measured thermal parameters and simulated wind velocity. The sensitivities for a large eddy simulation (LES) model and a delayed detached eddy simulation (DDES) model were tested in an idealized building array by Liu et al [23] and Liu and Niu [24].…”
Section: Introductionmentioning
confidence: 99%